Vsaka izkušnja, ki ostane nereflektirana, je izgubljena - Vodeb Bonač, Marta (Šolsko svetovalno delo, 2012)
Supervision as a learning method issuing from professional work continues to be met by mistrust. The paper is of illustrative nature and tries to make the reader understand the process of learning by experience in teaching profession. By combining the experiences of executing supervision for teachers, the author speaks about the reasons for supervision, about the basic characteristics of the method and about its course as well as about its effects upon the participants.
Keywords: izkustveno učenje; refleksija; stres; supervizija; učinki